Handball team staff heart rate monitoring during women's Champions League match - Bon, M.; Bracic, M.; Sibila, M.; Pori, P. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
The aim of the study was to analyze the heart rate of members of the coaching staff (head coach, two assistant coaches, (age 36 ± 3.39 years, height 178 ± 6.86cm, body mass 83,3 ± 5.23kg). We analyzed the values of 5 matches; one very important match between HC Gyor and HC Krim Mercator and three matches in the regional league and one training/friendly match. The heart rate (HR) was recorded at one-second intervals using the Polar Team System 2 (Polar Electro, Finland). It consisted of an electrode belt which recorded ECG signals without a wristwatch. The data stored in the belt was transferred to a PC and processed using the Polar Team2 software during the matches. Based on the data obtained from the coaching staff, the program displayed the heart rate trace (beats/min) and automatically estimated energy expenditure (kcal) with the reference to each individual`s data. The energy expenditure amounted to 476.0±258.9 kcal. The mean value of the heart rate for all the matches was 96.4±17.36 beats/min and the average 87,9 ±8,5 beats/min. The maximum recorded heart rate was 145 (head coach), the max HR in all matches was 119, 2±12,6 beats/min. The values of HR and energy expenditure of the head coach are higher than for both assistant coaches. Importance of the match has a big influence on the values of HR and energy expenditure